The Definition of Grammatical Agreement - SARGSYAN, ARTASHES (Bulletin of Yerevan University B: Philology, 2021)
The article presents several opinions about the definition of grammatical agreement and it mentions those circumstances that are omitted from the definition of agreement. In particular, it points the connection between the homogeneous parts of the sentence and the predicate, between those units that are not considered as a part of the sentence and between the components of the composite sentence. It is also pointed, that defining the grammatical agreement, one must take these factors into consideration.